Building Independence through an Entrepreneur Education, Marketing Channel Strategy and E-Commerce Mediated by Student’s Entrepreneur Motivation in Increasing MSMEs in Bekasi District - Harisandi, Prasetyo; Yahya, Adibah; Istiqomah, Anisah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study investigates the variables that affect the independence of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Bekasi District. It focuses on the importance of marketing strategy, e-commerce adoption, entrepreneur education, and entrepreneur motivation. Structured questionnaires were utilized to gather data from 156 MSME owners and students using a quantitative research approach. The data was analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique to test the proposed correlations. The results show that e-commerce usage, marketing strategy, and entrepreneur education all significantly increase MSME independence. Moreover, it was discovered that the correlations between these variables and MSME independence were mediated by entrepreneur motivation. The model fit indices highlight the validity and dependability of the study findings by showing that the structural model fits the data well. Policymakers, educators, and MSME owners aiming to encourage entrepreneurship and economic sustainability in Bekasi District and comparable places can benefit greatly from these findings.